Intraday Effect of News on Emerging European Forex Markets: An Event Study Analysis - Evžen Kocenda; Michala Moravcová (Center for Economic Studies and ifo Institute (CESifo), 2018)
We analyze the impact of Eurozone/Germany and U.S. macroeconomic news announcements and the communication of the monetary policy settings of the ECB and the Fed on the forex markets of new EU members. We employ an event study methodology to analyze intra-day data from 2011–2015. Our comprehensive analysis of the wide variety of macroeconomic information during the post-GFC period shows that: (i) macroeconomic announcements affect the value of the new-EU-country exchange rates, (ii) the origin of the announcement matters, (iii) the type of announcement matters, (iv) different types of news (good, bad, or neutral) result in different reactions, (v) markets react not only after the news release but also before, (vi) when the U.S. dollar is a base currency the impact of the news is larger than in the case of the euro, (vii) announcements on ECB monetary policy result in stronger effects than those of the Fed, (viii) temporary inefficiencies are present on new-EU-country forex markets, (ix) new-EU-country exchange rates react differently on positive US news during the EU debt crisis when compared to the rest of the period.
Keywords: C52; F31; F36; G15; P59; 330; foreign exchange markets; intraday data; abnormal returns; event study; macroeconomic announcements; monetary policy settings; European Union; new EU members